Changes in The Width of The Keratinised Mucosa in The Area of One-Stage Dental Implantation When Using a Soft Tissue Cuff Reinforced with Bone Grafting Material - Niezhentsev, Ye. Yu.; Chertov, S. O.; Чертов, Сергій Олександрович (My University, 2025)
Objectives: The aim of the paper is a follow-up comparison of the xenogenic collagen matrix and soft-tissue cuff reinforced with bone grafting material (STCRBGM) for an increase in the keratinized mucosa's width in the one-stage dental implantation area. Materials and Methods: The main observation group consisted of 25 patients who, after tooth extraction, had the implant placed in a prepared bed where the socket was preliminarily filled with Sensobone xenograft, after which the STCRBGM was formed with subsequent fixation of a temporary crown. The comparison group included 26 patients in whom, after tooth extraction, the implant was placed in the prepared bed where the socket was preliminarily filled with Sensobone xenograft, after which the soft tissue area was filled with Sensobone xenograft, and the temporary crown was fixed. The width of the keratinized mucosa (KM) was determined from the free gingival margin to the mucogingival junction before implantation, then 3-month and one-year follow-up after implantation. The study results were processed using the statistical package of the licensed software “Statistica, version 13”. Results: Comparing the follow-up use of xenogenic collagen matrix and STCRBGM to increase the width of the KM in the field of one-stage dental implantation, it was found that the use of STCRBGM provided a significant increase in the width of the KM in 3-month follow-up after implantation by 0.87 mm, and in one-year follow-up by 0.94 mm, which is significantly 1.25 mm more than in the group where only xenogenic collagen matrix was used. Besides, a significant increase in the width of the KM was observed in one-year follow-up in the area of all teeth and in the group with xenogenic collagen matrix there was a significant decrease. The KM width does not depend on the age and gender of the patients, as well as on the type of teeth and jaws. Conclusion: The effectiveness of one-stage dental implantation is facilitated by the adequate width of the KM provided by STCRBGM.
Keywords: One-moment dental implantation; Keratinized mucous membrane; Sensobone xenograft; Free connective tissue autograft